Show me the real world: reactions of American female consumers to more realistic and diverse human models in e-commerce - Plotkina, Daria; Saurel, Hélène (Journal of marketing theory and practice, 2021)
Product presentation on apparel webstores usually involves human models. Given the growing trend toward body realism, this research studies the impact of a female model's body size and its interaction with her pose and ethnicity on purchase intention in apparel e-retailing. The model's impact is explained by e-consumers' actual and ideal self-congruence. Two experimental studies show the willingness of American female e-consumers to purchase garments presented by more realistic and diversified models, challenging the White and thin Western stereotype. Thus, plus-size and naturally posed models increase purchase intention. Furthermore, White models do not guarantee better outcomes than nonwhite models.